Drug-Coated Balloons for Restenosis Prophylaxis - Speck, U.; Scheller, B.; Hamm, B. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Drug-coated balloons for restenosis prophylaxis provide a high local drug concentration with minimal or no systemic adverse effects. Their development was both delayed and facilitated by the introduction of drug-eluting stents: delayed because sustained release kinetics from stent platforms seemed to be essential and facilitated because prior experience with stents allowed selection of testing methods and drugs. Currently, a variety of drug-coated balloons are available, basically consisting of a coating containing paclitaxel at a dose of about 3 µg/mm² balloon surface, and different additives influencing the adherence and release of the drug, e. g., contrast agent, urea, or various amphiphilic compounds. The drug is almost completely released during a single inflation of 30 – 60 seconds. Studies in animals and several independent randomized clinical trials in coronary and peripheral arteries demonstrate effective reduction of neointimal proliferation, restenosis, and revascularization persisting for at least 2 years or 5 years according to one study in coronary arteries. Drug-coated balloons are preferably used for treating coronary in-stent restenosis and de novo and restenotic lesions in peripheral vessels. No coating-related adverse events have been observed in clinical trials. Persistent efficacy may be explained by the long residence time of paclitaxel in tissue or inhibition of an essential first step in the chain of events leading to neointimal proliferation.Citation Format:• Speck U., Scheller B., Hamm B. Drug-Coated Balloons for Restenosis Prophylaxis. Fortschr Röntgenstr 2014; 186: 348 – 358
Keywords: drug-coated balloon catheter; restenosis; peripheral arteries; paclitaxel; angioplasty; drug-coated balloon